INVESTASI KAS MASJID DALAM PERSPEKTIF SADD DAN FATH AL-DZARI’AH - amin kurniawan kurniawan; Muhammad Lathoif Ghozali (Universitas Muhammadiyah Surabaya, 2021)
Islamic economic and financial resources have enormous potential to contribute to the nation's economic development. Until now, Muslims have not been able to manage and empower it appropriately and professionally. For this reason, investing the mosque's cash is an alternative solution in its management. This article will discuss the mosque's cash investment activities which were analyzed using Sadd al-Dzari'ah and Fath al-Dzari'ah. This research is library research, with qualitative method through Usul Fiqh approach. Data analysis techniques in the form of data reduction, data presentation, and drawing conclusions. Based on the results of the analysis of the al-Dzari'ah concept, the mosque's cash investment activity brings far greater benefits than its benefits, so it is necessary to open the faucet as wide as possible based on the Fath al-Dzariah concept. On the other hand, there were irregularities and misuse of mosque cash which required the precautionary principle by applying the Sadd al-Dzariah concept. By managing mosque cash as an economic asset for the people properly, appropriately and professionally through investment, it is one of the roles that can be given by Muslims in contributing to improving the welfare and development of the nation.